2004
DOI: 10.1021/jf049147q
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electron Beam Irradiation and Storage at 5 °C on Thiobarbituric Acid Reactive Substances and Carbonyl Contents in Chicken Breast Meat Infused with Antioxidants and Selected Plant Extracts

Abstract: This study evaluated the effectiveness of synthetic and natural antioxidants, green tea, commercial grape seed extracts/combinations, and TBHQ, with varying concentrations of lipid oxidation of nonirradiated and irradiated chicken breast meats stored at 5 degrees C for 12 days. Fresh boneless and skinless chicken breast meats were vacuum-infused with varying concentrations of antioxidants: green tea, grape seed extracts alone/in combination, and TBHQ. The irradiation dosage was 3.0 kGy. Carbonyl values of raw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 14 publications
1
25
0
3
Order By: Relevance
“…Mielnik et al [9] demonstrated that grape seed extract was effective in inhibiting lipid oxidation of cooked turkey meat during chill-storage. Rababah et al [10] reported that GSE is an effective antioxidant to minimize irradiation-induced lipid oxidation developments of breast meats. GSE can be used to stabilize sunflower oils [11].…”
Section: Introductionmentioning
confidence: 99%
“…Mielnik et al [9] demonstrated that grape seed extract was effective in inhibiting lipid oxidation of cooked turkey meat during chill-storage. Rababah et al [10] reported that GSE is an effective antioxidant to minimize irradiation-induced lipid oxidation developments of breast meats. GSE can be used to stabilize sunflower oils [11].…”
Section: Introductionmentioning
confidence: 99%
“…Some plant extracts have been evaluated for their properties as natural antioxidants (YEN;CHEN, 1995;LOPEZ-BOTE et al, 1998;LEE;SHIBAMOTO, 2002;BASMACIOGLU;TOKUSOGLU;ERGUL, 2004;RABABAH et al, 2004), which is mainly attributed to the flavonoids present in the plants. Some extracts were classified by Lee and Shibamoto (2002) The antibacterial and antioxidant effect of rosemary, evaluated in vitro, was investigated by Asolini, Tedesco and Carpes (2006) and Klancnik, Guzej, and Kolar (2009), who observed that the result was dependent on the concentration of solute and solvent used.…”
Section: Microbiological Analysesmentioning
confidence: 99%
“…Studies have shown that addition of phenolic-rich plant extracts prevents protein carbonyl accumulation during storage of fresh meat (Jia, Kong, Liu, Diao, & Xia, 2012;Rababah et al, 2004;Rodríguez-Carpena, Morcuende, Andrade, Kylli, & Estévez, 2011;. However, the protection is inferior to what is commonly observed for lipid oxidation as recently demonstrated in fresh beef patties added a white grape extract (Jongberg, Skov, Tørngren, Skibsted, & Lund, 2011), and in some cases no effect or prooxidative effect of adding plant extracts to fresh meat or meat products have been found .…”
Section: Introductionmentioning
confidence: 99%